A method for producing lithium sulfide
Patent Information
- Application Number
- CN202611091231.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]有鉴于此,针对上述现有技术中存在的反应安全性差、产品纯度波动大、杂质难去除及收率偏低的综合缺陷,本发明提供一种硫化锂及其制备方法,通过引入LiAlxSiyOz补锂剂并对制备工艺进行优化及控制,同步实现强脱水作用,抑制水解且不引入金属杂质,获得高纯度、颗粒均匀、高收率的硫化锂产品
本发明通过引入高孔隙率亚微米多孔颗粒,利用其强脱水、晶型导向和防团聚的多重协同效应,并配合优化的分段升温制度与深度脱气步骤,使收率提升至接近定量转化的水平,结晶度达到高结晶态,纯度提升至高纯级别,水分大幅降低至痕量水平,粒径细化至亚微米级且分布均匀可控,全面解决了现有工艺收率低、纯度差、水分高和颗粒团聚严重的技术瓶颈。
Smart Images

Figure FT_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic lithium compound preparation technology, specifically a method for preparing lithium sulfide. Background Technology
[0002] Lithium sulfide (Li₂S) is the core lithium source material for constructing sulfide solid electrolytes and an indispensable key precursor for lithium-sulfur batteries. Its physicochemical parameters—including purity grade, particle size distribution, impurity content, and preparation yield—directly determine the manufacturing cost and electrochemical performance of downstream batteries. Therefore, developing an industrial-scale production technology for lithium sulfide that is both economical and reliable has become one of the key breakthroughs in promoting the industrialization of all-solid-state batteries.
[0003] Currently, all mainstream preparation routes for lithium sulfide have defects, specifically: (1) Direct synthesis of lithium sulfide: expensive raw materials, poor safety, and limited scale-up; (2) Carbothermic reduction of lithium sulfate: many byproducts, difficulty in achieving 99.9% purity, and high metal impurities; (3) Hydrogen sulfide + lithium hydroxide: easily hydrolyzed to generate LiOH. H2O, LiHS, and Li2CO3 have low product purity, particle agglomeration, and yields of only 82%–88%, making it difficult to meet industrial needs. Summary of the Invention
[0004] In view of this, and addressing the combined shortcomings of the existing technologies, such as poor reaction safety, large fluctuations in product purity, difficulty in removing impurities, and low yield, this invention provides a lithium sulfide and its preparation method, which introduces LiAl... x Si y O z The lithium supplementation agent is used to optimize and control the preparation process, simultaneously achieving strong dehydration, inhibiting hydrolysis without introducing metal impurities, and obtaining high-purity, uniformly sized, and high-yield lithium sulfide products.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention discloses a method for preparing lithium sulfide, comprising the following steps: S1, LiAl x Si y O z Porous particles are mixed with lithium salt, and then an organic solvent is added for homogenization to obtain a fluid solid-liquid mixed reaction precursor. S2. Under an inert atmosphere, the solid-liquid mixed reaction precursor is heated to 160-180°C and a sulfur-containing gas is introduced to react and generate an intermediate product containing lithium sulfide. S3. Under the conditions of maintaining a protective atmosphere and sulfur-containing gas partial pressure, the intermediate product is kept at a constant temperature to remove residual hydroxyl and carbonate impurities in the crystal lattice, thereby obtaining purified crude lithium sulfide. S4. The crude lithium sulfide is post-processed to obtain high-purity lithium sulfide powder.
[0006] As a further aspect of the present invention: LiAl x Si y O z x, y, z in the equation simultaneously satisfy 1≤x≤2, 2≤y≤4, and z=2x+2y.
[0007] As a further aspect of the present invention: the LiAl x Si y O z It is 1% to 3% of the mass of lithium salt.
[0008] As a further aspect of the present invention: the lithium salt, LiAl x Si y O z The total solid-liquid mass ratio of the solid to the organic solvent is 1:1.5 to 9.
[0009] As a further aspect of the present invention: LiAl x Si y O z It is submicron in size, with a particle size D50 of 0.5–0.7 μm, a porosity ≥92%, and a pore size of 0.8–2 nm.
[0010] As a further embodiment of the present invention: the sulfur-containing gas is H2S gas, the flow rate of the sulfur-containing gas in step S2 is 3-4 L / min; the flow rate of the sulfur-containing gas in step S3 is 0.2-0.5 L / min, and the ventilation time is 5-10 min.
[0011] As a further aspect of the present invention: the heating is a stepped multi-stage heating, specifically: the first stage is heated to 100-110℃ and held for 10-30 minutes; the second stage is heated to 120-130℃ and held for 20-30 minutes; the third stage is heated to 160-180℃ and held for 30-50 minutes.
[0012] As a further aspect of the present invention, the post-processing includes washing, crushing, and sieving.
[0013] Secondly, the present invention discloses lithium sulfide prepared by the preparation method described above, which has a molar yield ≥99.8%, crystallinity ≥99.7%, particle size D50 of 2.5~3.4um, purity ≥99.99%, and moisture content ≤41ppm.
[0014] Compared with the prior art, the beneficial effects of the present invention are: This invention introduces high-porosity submicron porous particles, utilizing their strong dehydration, crystal orientation, and anti-agglomeration synergistic effects. Combined with an optimized segmented heating regime and deep degassing steps, the yield is increased to near-quantitative conversion levels, crystallinity reaches a high crystalline state, purity is improved to a high purity level, moisture is significantly reduced to trace levels, and particle size is refined to the submicron level with uniform and controllable distribution. This invention comprehensively solves the technical bottlenecks of existing processes, such as low yield, poor purity, high moisture content, and severe particle agglomeration.
[0015] The results show that the present invention has successfully achieved efficient and controllable synthesis of high-purity lithium sulfide through synergistic optimization of additives and processes. The product indicators fully meet the stringent requirements of sulfide solid electrolytes for lithium sources, and the process route is safe and reliable, with significant industrial application value. Attached Figure Description
[0016] Figure 1 The XRD pattern of the lithium sulfide material prepared in Example 1 of this invention is shown. This pattern highly matches the lithium sulfide crystal structure in the standard card PDF# 23-0369. From the spectral characteristics, the sample exhibits multiple sharp diffraction peaks at positions such as 2θ ≈ 27°, 31°, 45°, 53°, 66°, and 72°. These peak positions completely correspond to the characteristic diffraction peaks of Li₂S in the standard card, indicating that the sample has good crystallinity and that the main phase is pure Li₂S without obvious impurity peaks. Among them, the strongest peak at 2θ ≈ 27° corresponds to the (111) crystal plane of Li₂S and is its most representative diffraction peak. Detailed Implementation
[0017] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0019] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional methods in the prior art, and therefore will not be described in detail; unless otherwise specified, the parts in the following embodiments refer to parts by weight.
[0020] Example 1 (1) Take 100g of anhydrous lithium hydroxide, add 1.0g of LiAlSi2O6 submicron porous particles (D50=0.5μm, porosity 92.67%, pore size 0.8~1.5nm), and then add 160g of NMP solvent to homogenize to obtain a solid-liquid precursor. (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 100℃ for 25 min, heated to 120℃ for 26 min, and then heated to 160℃ for 48 min. H2S gas (flow rate of 3.2 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion; and an intermediate product rich in lithium sulfide was obtained. (3) Continue to pass H2S gas (0.2 L / min, 10 min) into the intermediate product obtained in step (2) to remove residual hydroxyl groups and carbonate impurities to obtain crude Li2S. (4) The crude Li2S product is obtained by washing, separating, drying, crushing and passing through a 600-mesh sieve.
[0021] Example 2 (1) Take 100g of anhydrous lithium hydroxide and add 1.5g of LiAl 1.02 Si 2.02 O 6.08 Submicron porous particles (D50=0.6μm, porosity 93.11%, pore size 0.9~1.8nm) were then homogenized with 200g of NMP solvent to obtain a solid-liquid precursor. (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 105℃ for 20 min, heated to 130℃ for 22 min, and then heated to 165℃ for 45 min. H2S gas (flow rate of 3.5 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion; and an intermediate product rich in lithium sulfide was obtained. (3) Continue to pass H2S gas (0.25 L / min, 8 min) into the intermediate product obtained in step (2) to remove residual hydroxyl groups and carbonate impurities to obtain crude Li2S. (4) The crude Li2S product is obtained by washing, separating, drying, crushing and passing through a 700-mesh sieve.
[0022] Example 3 (1) Take 100g of anhydrous lithium hydroxide and add 2g of LiAl 1.03 Si 2.02 O 6.1 Submicron porous particles (D50=0.55μm, porosity 92.86%, pore size 0.8~1.8nm) were then homogenized with 220g of NMP solvent to obtain a solid-liquid precursor. (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 110℃ for 15 min, heated to 120℃ for 25 min, and then heated to 170℃ for 35 min. H2S gas (flow rate of 3.2 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion; and an intermediate product rich in lithium sulfide was obtained. (3) Continue to pass H2S gas (0.3L / min, 7min) into the intermediate product obtained in step (2) to remove residual hydroxyl groups and carbonate impurities to obtain crude Li2S. (4) The crude Li2S product is obtained by washing, separating, drying, crushing and passing through a 600-mesh sieve.
[0023] Example 4 (1) Take 100g of anhydrous lithium hydroxide and add 2.5g of LiAlSi 2.02 O 6.04 Submicron porous particles (D50=0.6μm, porosity 93.19%, pore size 1~1.8nm) were then homogenized with 300g of NMP solvent to obtain a solid-liquid precursor. (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 100℃ for 28 min, heated to 125℃ for 22 min, and then heated to 175℃ for 32 min. H2S gas (flow rate of 3.5 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion; and an intermediate product rich in lithium sulfide was obtained. (3) Continue to pass H2S gas (0.4 L / min, 6 min) into the intermediate product obtained in step (2) to remove residual hydroxyl groups and carbonate impurities to obtain crude Li2S. (4) The crude Li2S product is obtained by washing, separating, drying, crushing and passing through an 800-mesh sieve.
[0024] Example 5 (1) Take 100g of anhydrous lithium hydroxide and add 3g of LiAl 1.02 Si2O 6.08 Submicron porous particles (D50=0.7μm, porosity 93.21%, pore size 1.2~2nm) were then homogenized with 500g of NMP solvent to obtain a solid-liquid precursor. (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 110℃ for 12 min, heated to 130℃ for 20 min, and then heated to 180℃ for 30 min. H2S gas (flow rate of 4 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion; and an intermediate product rich in lithium sulfide was obtained. (3) Continue to pass H2S gas (0.5L / min, 5min) into the intermediate product obtained in step (2) to remove residual hydroxyl groups and carbonate impurities to obtain crude Li2S. (4) The crude Li2S product is obtained by washing, separating, drying, crushing and passing through an 800-mesh sieve.
[0025] Comparative Example 1 (1) Take 100g of anhydrous lithium hydroxide, add 200g of organic solvent, mix well to obtain a solid-liquid precursor; (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 120℃ for 30 min, then heated to 180℃ and kept for 60 min. H2S gas (flow rate of 4 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion and obtain intermediate products rich in lithium sulfide. (3) Continue to pass H2S gas into the intermediate product obtained in step (2) (flow rate of 4L / min, and cool it with the furnace after the holding time is over, without setting a separate deep impurity removal step) to obtain crude Li2S; (4) The crude Li2S product is washed, separated, crushed and sieved through an 800-mesh sieve to obtain the finished Li2S product.
[0026] Comparative Example 2 (1) Take 100g of anhydrous lithium hydroxide, add 300g of organic solvent, mix well to obtain a solid-liquid precursor; (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 125℃ for 28 min, then heated to 190℃ and kept for 50 min. H2S gas (flow rate of 3.5 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion and obtain intermediate products rich in lithium sulfide. (3) Continue to pass H2S gas into the intermediate product obtained in step (2) (flow rate of 3.5 L / min, and cool it with the furnace after the holding time is over, without setting a separate deep impurity removal step) to obtain crude Li2S; (4) The crude Li2S product is washed, separated, crushed and sieved through an 800-mesh sieve to obtain the finished Li2S product.
[0027] Comparative Example 3 (1) Take 100g of anhydrous lithium hydroxide, add 500g of organic solvent, mix well to obtain a solid-liquid precursor; (2) The solid-liquid precursor was heated in stages under an inert atmosphere: it was kept at 130℃ for 25 min, then heated to 185℃ and kept for 55 min. H2S gas (flow rate of 3.8 L / min) was introduced throughout the process to carry out gas-solid neutralization conversion and obtain intermediate products rich in lithium sulfide. (3) Continue to pass H2S gas into the intermediate product obtained in step (2) (flow rate of 3.8 L / min, and cool it with the furnace after the holding time is over, without setting a separate deep impurity removal step) to obtain crude Li2S; (4) The crude Li2S product is washed, separated, crushed and sieved through an 800-mesh sieve to obtain the finished Li2S product.
[0028] Test case The final products obtained from each embodiment and comparative example were subjected to performance tests, and the test results are shown in Table 1.
[0029] Table 1
[0030] As can be clearly seen from the data in Table 1, the various embodiments of the present invention introduce LiAl... x Si y O z With the addition of submicron porous particles and an optimized segmented heating and deep degassing process, the overall performance of the product is significantly better than that of the comparative example without the additive: the yields of Examples 1-5 are as high as 99.83%-99.86%, the crystallinity is 99.74%-99.77%, the purity is above 99.995%, the moisture content is controlled at 38.47-40.13 ppm, and the D50 particle size is refined to 2.5-3.5 μm, achieving uniformity. The controllable micron-sized particle distribution was achieved. However, Comparative Examples 1-3, due to the lack of porous additives and independent deep impurity removal steps, had yields of only 86.81%-87.44%, crystallinity of only 88.76%-89.26%, purity of only 99.576%-99.584%, moisture content as high as 166.84-168.17 ppm, and D50 particle size as large as 11.7-12.3 μm. All indicators were far inferior to those of the examples. This fully demonstrates that the LiAlxSiyOz submicron porous particles introduced in this invention not only exert a strong dehydration, hydrolysis inhibition, and anti-agglomeration effect due to their ultra-high porosity and nanoscale pore size, but also significantly improve the crystallinity of Li2S through the crystal orientation effect. Combined with a precise segmented heating regime and subsequent low-flow-rate deep degassing, they jointly achieve excellent results with a yield exceeding 99.5%, a purity of over 99.99%, a moisture content of less than 50 ppm, and a uniform particle size controllable within the range of 2.4~3.6 μm. This effectively overcomes the technical bottlenecks of low yield, poor purity, and severe particle agglomeration in traditional processes, providing a reliable technical solution for the industrial production of high-purity lithium sulfide for sulfide solid electrolytes.
[0031] Although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
[0032] Therefore, the above description is only a preferred embodiment of this application and is not intended to limit the scope of this application; that is, all equivalent modifications made in accordance with the scope of the claims of this application shall be within the protection scope of the claims of this application.
Claims
1. A method for preparing lithium sulfide, characterized in that, Includes the following steps, S1, LiAl x Si y O z Porous particles are mixed with lithium salt, and then an organic solvent is added for homogenization to obtain a fluid solid-liquid mixed reaction precursor. S2. Under an inert atmosphere, the solid-liquid mixed reaction precursor is heated to 160-180°C and a sulfur-containing gas is introduced to react and generate an intermediate product containing lithium sulfide. S3. Under the conditions of maintaining a protective atmosphere and sulfur-containing gas partial pressure, the intermediate product is kept at a constant temperature to remove residual hydroxyl and carbonate impurities in the crystal lattice, thereby obtaining purified crude lithium sulfide. S4. The crude lithium sulfide is post-processed to obtain high-purity lithium sulfide powder.
2. The preparation method according to claim 1, characterized in that, LiAl x Si y O z x, y, z in the equation simultaneously satisfy 1≤x≤2, 2≤y≤4, and z=2x+2y.
3. The preparation method according to claim 1, characterized in that, The LiAl x Si y O z It is 1% to 3% of the mass of lithium salt.
4. The preparation method according to claim 1, characterized in that, The lithium salt, LiAl x Si y O z The total solid-liquid mass ratio of the solid to the organic solvent is 1:1.5 to 9.
5. The preparation method according to claim 1, characterized in that, LiAl x Si y O z It is submicron in size, with a particle size D50 of 0.5–0.7 μm, a porosity ≥92%, and a pore size of 0.8–2 nm.
6. The preparation method according to claim 1, characterized in that, The sulfur-containing gas is H2S gas. In step S2, the flow rate of the sulfur-containing gas is 3-4 L / min; in step S3, the flow rate of the sulfur-containing gas is 0.2-0.5 L / min, and the ventilation time is 5-10 min.
7. The preparation method according to claim 1, characterized in that, The heating is a stepped, multi-stage heating process, specifically: the first stage heats up to 100-110℃ and holds for 10-30 minutes; the second stage heats up to 120-130℃ and holds for 20-30 minutes; the third stage heats up to 160-180℃ and holds for 30-50 minutes.
8. The preparation method according to claim 1, characterized in that, The post-processing includes washing, crushing, and sieving.
9. The lithium sulfide prepared by the method according to any one of claims 1-8, characterized in that, Its molar yield is ≥99.8%, crystallinity is ≥99.7%, particle size D50 is 2.5~3.4um, purity is ≥99.99%, and moisture content is ≤41ppm.